Surveillance of unplanned return to the operating theatre in neurosurgery combined with a mortality–morbidity conference: results of a pilot survey. Issue 5 (10th February 2012) - Marini, Hélène; Merle, Véronique; Derrey, Stéphane; Lebaron, Christine; Josset, Valérie; Langlois, Olivier; Gilles Baray, Marie; Frébourg, Noëlle; Proust, François; Czernichow, Pierre
Abstract : Background: Unplanned return to the operating theatre (UROT) is a useful trigger tool that could be used to identify surgical adverse events (SAEs). The present study describes the feasibility of SAE surveillance in neurosurgical patients, based on UROT identification, completed with SAE analysis at a morbidity–mortality conference (MMC) meeting. Method: For consecutive patients who underwent a neurosurgical procedure between 1 November 2008 and 30 April 2009, return to the operating theatre (ROT) was identified based on the hospital information system associated to prospective payment (HISPP). ROT was classified as planned or unplanned and UROT was further classified as related to the natural history of the disease or related to an adverse event (AE-UROT). MMC meetings were organised to discuss results of UROT surveillance and to analyse AE-UROT. Results: 1006 neurosurgical procedures were included in the surveillance. HISSP identified 152 ROTs, with 73 UROTs related to an SAE (7.3% (5.7% to 9.0%)): infectious SAE (n=24, 2.4% (1.5% to 3.5%)), haemorrhagic SAE (n=23, 2.3% (1.5% to 3.4%)), other cause SAE (n=26, 2.8% (1.9% to 4.0%)), and infectious and other cause SAE (n=2, 0.2% (0.0% to 0.7%)). Identification of AE-UROT through HISSP required a 4 h/month time frame. Eight UROTs related to SAE cases were discussed during MMC meetings, leading to the identification of non-conforming care processes and practical improvement actions. Conclusion: UROT related to SAE surveillance in neurosurgical patients was considered feasible. The association of surveillance and MMCs allowed staff to concentrate on the analysis of most frequent or most severe AEs and was a practical and useful tool to stimulate improvement. The impact on healthcare quality of SAE surveillance associated with MMC warrants further research.